THE CORRELATION BETWEEN THE PARENTAL ATTENTION AND STUDY TIME AT HOME WITH THE RESULTS OF LEARNING MATHEMATICS - Siti Bunayah; Uus Kusdinar (Universitas Ahmad Dahlan, 2019)
Student learning mathematics results relate to many factors. Interest in learning, learning independence, and learning a facility are some of the factors suspected to be related to learning outcomes. This study aims to determine whether there is a positive and significant relationship between parental attention and study time at home with the results of a learning mathematics students of class VIII odd semester SMP Muhammadiyah 6 Yogyakarta in the academic year 2017/2018. This study's population are all students of class VIII odd semester Junior High School (SMP) Muhammadiyah 6 Yogyakarta in the academic year 2017/2018 consisting of four classes with 106 students. Samples were taken by random sampling technique and obtained class VIII A, consisting of 28 students. Data collection techniques used questionnaires and test techniques. Test of research instrument using validity test, reliability test, and test of different power. Existence prerequisite tests include normality tests, independent tests, and linearity tests. To analysis the data, the researcher using correlation analysis and linear regression analysis. The results showed that there was a positive and significant correlation between learning parental attention ( ) and learning study time at home ( ) with students' mathematics learning result with ie 4,301> 3.37 with R = 0,506 and R2 = 0,256 with Y = 19,368 + 0,307 + 0,360 , and RC ( ) = 53,539 % and RC ( ) = 46,461%, EC ( ) = 13,305% and EC ( ) = 11,199%.